HUBUNGAN PARTUS LAMA DENGAN KEJADIAN ASFIKSIA DI RUANG PERINATOLOGI RSUD INDRAMAYU TAHUN 2020 - Lusi Febrina; Rosalia Rahayu; Wahyudin (Jurnal Kesehatan Mahardika, 2020)
Asphyxia is a condition where a newborn baby cannot breathe spontaneously or experience respiratory failure. The event of asphyxia can be caused by the length of labor. Long parturition will cause infection, exhaustion, dehydration in the mother, sometimes post partum bleeding can occur which can cause maternal death. In the fetus there will be infections, injuries and asphyxia which can increase infant mortality. This study aims to determine the relationship between long parturition with asphyxia in the Perinatology Room of Indramayu Regional Hospital in 2020  This type of research is descriptive correlation using cross sectional approach. The population in this study were all infants with asphyxia at Indramayu Regional Hospital in January-March 2020, totaling 265 patients with a sample of 73 patients. The sampling technique used was consecutive sampling. The instrument of this study was the checklist sheet, and the data analysis used the chi square test, the significance value α = 0.05.  The results of the study It is known that labor with long parturition is 50 (68.5%), the incidence of asphyxia asphyxia is as much as 35 (47.9%) cases, the hypothesis test is obtained p value of 0.022 which means there is a relationship between long parturition and the incidence of asphyxia in Perinatology Room of Indramayu Regional Hospital.